A Case Study on Cloud Migration and Improvement of Twelve-Factor App - Peltotalo, Miika (My University, 2021)
The Twelve-Factor app methodology was introduced in 2011, intending to raise awareness, provide shared vocabulary and offer broad conceptual solutions. In this thesis, a case study was done on two software implementations of the same business idea. The implementations were introduced and then analyzed with Twelve-Factor. Hevner's Information Systems Research Framework was used to assess the implementations, and Twelve-Factor's theoretical methodology was combined with them to form results. The implementations were found to fulfill most of the twelve factors, although in different ways. The use of containers in the new implementation explained most of the differences. Some factors were also revealed to be standard practices today, which showed the need to abstract factors like Dependencies, Processes, Port binding, Concurrency, and Disposability. In addition, the methodology itself was analyzed, and additions to it were introduced, conforming to the modern needs of applications that most often run containerized on cloud platforms. New additions are API First, Telemetry, Security, and Automation. API First instructs developers to prioritize building the APIs at the start of the development cycle, while Telemetry points that as much information as possible should be collected from the app to improve performance and help to solve bugs. Security introduces two different practical solutions and a guideline of following the principle of least privilege, and lastly, automation is emphasized to free up developer time.

Twelve-Factor App on vuonna 2011 julkaistu metodologia, jonka tarkoituksena on nostaa tietoisuutta, tarjota jaettu sanakirja alan termistölle sekä tarjota yleinen käsitteellinen ratkaisu. Tässä työssä esitellään kaksi toteutusta samasta liiketoimintaideasta. Toteutukset esitellään ja ne analysoidaan Twelve-Factorin avulla. Hevnerin Information Systems Research Framework -mallia hyödynnettiin toteutusten arvioinnissa ja se yhdistettiin Twelve-Factor -mallin kanssa, jotta saatiin tulokset. Työssä huomattiin, että suurin osa Twelve-Factorin kuvaamista osista toteutuivat ohjelmistoja tarkasteltaessa. Toteutuksissa oli kuitenkin eroa. Etenkin Docker konttien käyttäminen uudessa toteutuksessa selitti suurimman osan eroista. Twelve-Factorin osien toteutuminen suurilta osin näytti tarpeen abstrahoida osia mallista, jotka ovat jo tavanomaisia käytäntöjä. Sen lisäksi metodologia itsessään analysoidaan ja siihen esitettiin lisäyksiä, jotta se vastaisi nykyaikaisten ohjelmistotuotteiden tarpeisiin, jotka ovat useimmiten kontitettuina eri pilvipalveluissa.Uusia lisäyksiä ovat API ensin -ajattelu, telemetria, tietoturva ja automaatio. API ensin -ajattelu ohjeistaa kehittäjiä priorisoimaan rajapintojen rakentamisen mahdollisimman aikaisessa vaiheessa ohjelmistoprojektia, kun taas telemetria ohjeistaa keräämään mahdollisimman paljon tietoa ohjelmiston toiminnasta, jotta voidaan kehittää tuotteen suoritustehokkuutta sekä helpottaa ohjelmistovirheiden ratkaisemista. Tietoturva esittelee kaksi erilaista käytännön ratkaisua sekä ohjenuoran noudattaa vähimpien oikeuksien periaatetta. Viimeisimpänä automaation tärkeyttä painotetaan, jotta säästetään ohjelmistokehittäjien aikaa ja ohjataan resursseja varsinaiseen arvon luomiseen.
Keywords: Twelve, factor, app, methodology, architecture, AWS, best practices